The Influence of Brand Ambassadors and Promotions on Purchase Decisions Through Brand Image as an Intervening Variable in Tokopedia E-Marketplace in East Java - Ali Mauludi AC; Nik Haryanti; In'am Nabila Klisty Putri (Universitas Pendidikan Ganesha, 2023)
This research was motivated by the rapid growth of e-commerce in Indonesia in 2019, which placed the country as the leader with 78% growth, followed by Mexico with 59%. In this context, several factors are of concern, including the role of brand ambassadors, promotion, and brand image. The main purpose of this study is to measure the direct and indirect influence of brand ambassadors and promotions on purchasing decisions through intervening variables, namely brand image, especially on the Tokopedia e-marketplace platform in East Java, Indonesia. This research is a type of comparative causal research with a quantitative approach. The population in this study is users of the Tokopedia e-marketplace application in the East Java region, with a sample of 100 respondents. The primary data collection method was carried out through the distribution of questionnaires through various social media. The collected data is then analyzed using multiple linear regression methods. The main results of the study show that brand ambassadors and promotions have a significant influence on consumer purchasing decisions through brand image on the Tokopedia e-marketplace platform. Brand ambassadors who have strong credibility and influence can help build positive consumer perceptions of the brand and products it represents. Meanwhile, promotions also play an important role in influencing consumers' purchasing decisions by providing special offers and other incentives. The results of this study provide new insights for e-commerce companies in developing effective marketing strategies to increase consumer satisfaction and business growth in today's digital era.